2021
DOI: 10.1007/s00167-021-06617-5
|View full text |Cite
|
Sign up to set email alerts
|

Cementless unicompartmental knee arthroplasty results in higher pain levels compared to the cemented technique: a prospective register study

Abstract: Purpose In recent years, the preferred fixation method for unicompartmental knee arthroplasty (UKA) has changed from cemented to cementless. The aim of this study was to compare patient-reported outcome measures (PROMs) from the cemented versus cementless techniques two- and twelve-months post-operation. Methods From 2015 to 2019, 187 cemented and 261 cementless UKAs were included based on an institutional registry. The Oxford Unicompartmental Knee System™… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, pain after knee replacement has always been an important factor of restricting knee replacement effect [ 17 ], lived around joints in knee surgery is a cocktail drugs can effectively alleviate postoperative pain, and is compared with femoral nerve block and vertebral canal or intravenous patient controlled analgesia, has little influence on quadriceps, benefit patients early postoperative activities, avoid wrestling and reduce opioid nausea, lethargy and other adverse reactions [ 18 , 19 ]. When choosing a drug cocktail, different joint surgeons take different drug cocktail formulations for different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, pain after knee replacement has always been an important factor of restricting knee replacement effect [ 17 ], lived around joints in knee surgery is a cocktail drugs can effectively alleviate postoperative pain, and is compared with femoral nerve block and vertebral canal or intravenous patient controlled analgesia, has little influence on quadriceps, benefit patients early postoperative activities, avoid wrestling and reduce opioid nausea, lethargy and other adverse reactions [ 18 , 19 ]. When choosing a drug cocktail, different joint surgeons take different drug cocktail formulations for different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Exposing only the diseased compartment without cutting the quadriceps muscle also avoids damage to the knee extension function, facilitates postoperative rehabilitation, and reduces adverse effects [19]. It allows accurate prosthesis placement, avoiding collision of ligaments and prosthesis; it allows complete removal of excess bone cement, reducing complications [20]. The unicondylar knee prosthesis replaces only the medial compartment of the knee joint without damaging the lateral compartment and without affecting the normal knee struc-ture.…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%
“…In a prospective cohort study, Gifstad et al 11 found significantly higher activity- and rest-related pain scores in the first year after cementless medial UKA compared to cemented cases. Using a large registry cohort, we were unable to replicate these results.…”
Section: Discussionmentioning
confidence: 98%